The Pronouncation Erros Interferences of Nias L1 in L2 - Asniar Duha; Line Sihombing; Sumarsih Sumarsih (LINGUISTIK TERAPAN, 2014)
This study is aimed to find out the factors in the pronunciation errors interference of Nias (First language; L1) with Indonesian as a (Second language; L2). The objectives of the study is to see how affect pronounciation errors interference of Niasnese L1 In Indonesian as a L2, to describe the types of pronunciation errors interference dominantly used by Niasnese speakers in Nias L1 In Indonesian as a L2 and understand why the pronounciation errors interference happen to the Niasnese in Indonesian as a L2. This research used a qualitative research to find out pronunciation errors interference of Niasnese native speakers. The data obtained from ten students and the parents of Nias speakers as the samples. Based on the observation result, it is found that the pronunciation errors interference at Nias in Indonesian as a L2: Deletion, addition and blends. There are three factors affect the Niasnese pronunciation error interference in Indonesian as a L2 in Sibolga, they are Intermarriage ( same culture marriage), The sound and the letters differences between Nias Language and Indonesian, Parents speak Nias language to the children or mother tongue, environment. Keyword : Errors, Interferenc, and Pronunciation.